Molecular Cytogenetic and Agronomic Characterization of the Similarities and Differences Between Wheat–Leymus mollis Trin. and Wheat–Psathyrostachys huashanica Keng 3Ns (3D) Substitution Lines - Li, Jiachuang; Li, Jiaojiao; Cheng, Xueni; Zhao, Li; Yang, Zujun; Wu, Jun; Yang, Qunhui; Chen, Xinhong; Zhao, Jixin (Frontiers in Plant Science, 2021)
Abstract Psathyrostachys huashanica Keng (2n = 2x = 14, NsNs) and Leymus mollis Trin. (2n = 4x = 28, NsNsXmXm) are valuable resources for wheat breeding improvement since they share the Ns genome, which contains diverse resistance genes. To explore the behaviors and traits of Ns chromosomes from the two species in wheat background, a series of wheat–P. huashanica and wheat–L. mollis substitution lines were developed. In the present study, line DH109 (F7 progeny of wheat–P. huashanica heptaploid line H8911  durum wheat Trs-372) and line DM131 (F8 progeny of wheat–L. mollis octoploid line M842  durum wheat Trs-372) were selected. Cytological observation combined with genomic in situ hybridization experiments showed that DH109 and DM131 each had 20 pairs of wheat chromosomes plus a pair of alien chromosome (Ns chromosome), and the pair of alien chromosome showed stable inheritance. Multiple molecular markers and wheat 55K SNP array demonstrated that a pair of wheat 3D chromosome in DH109 and in DM131 was substituted by a pair of P. huashanica 3Ns chromosome and a pair of L. mollis 3Ns chromosome, respectively. Fluorescence in situ hybridization analysis confirmed that wheat 3D chromosomes were absent from DH109 and DM131, and chromosomal FISH karyotype of wheat 3D, P. huashanica 3Ns and L. mollis 3Ns were different. Moreover, the two lines had many differences in agronomic traits. Comparing with their wheat parents, DH109 expressed superior resistance to powdery mildew and fusarium head blight, while DM131 had powdery mildew resistance, longer spike and more tiller number. Therefore, Ns genome from P. huashanica and L. mollis might has some different effects. The two novel wheat–alien substitution lines provides new ideas and resources for disease-resistance and high-yield breeding on further utilization of 3Ns chromosomes of P. huashanica or L. mollis.